Preference Aggregation With Incomplete Information - Chambers, Christopher P.; Hayashi, Takashi (Econometrica, 2014)
We show in an environment of incomplete information that monotonicity and the Pareto property applied only when there is common knowledge of Pareto dominance imply (i) there must exist a common prior over the smallest common knowledge event, and (ii) aggregation must be ex ante and ex post utilitarian with respect to that common prior and individual von Neumann–Morgenstern utility indices.